The ancients and Shakespeare on time : some remarks on the war of generations - Nowak, Piotr, 1966- (Value Inquiry Book Series, 2014)
In The Ancients and Shakespeare on Time Piotr Nowak depicts a world where tradition - devoid of gravity, "Sans teeth, sans eyes, sans taste, sans everything" - attempts to curb the young and new, while youth resists with all its power, vitality and characteristic insolence. The wars of generations, which Nowak explores in the works of Plato, Aristophanes and Shakespeare, pertain to the essence and meaning of time. They make up the dramatic tensions in the transgenerational dialogue between the old and the young.